KECEPATAN GELOMBANG GESER (VS) DAN KETEBALAN SEDIMEN (H) DI KABUPATEN KLATEN DARI DATA MIKROTREMOR - Anggit Mas Arifudin (TEKNISIA, 2021)
Research on Shear Wave Velocity (vs) and Sediment Thickness (h) in Klaten Regency, Central Java from field microtremor data aims to determine the thickness of sediment or soft sediment as one of the factors of high and low earthquake vulnerability. Microtremor data was collected using a three-component TDS 303 seismometer, covering 111 measuring points in the Klaten Regency area. In this study, the sediment thickness was calculated using the equation shear wave velocity (vs) divided by four times the dominant frequency (fg). The dominant frequency (fg) value is obtained from the HVSR curve while the shear wave velocity value (vs) used in this study is the inversion value of the HVSR curve which is modeled based on borlog data at the Wedi Church, equated for all measurement points. On the map of the shear wave velocity distribution at each microtremor measuring point has a vs value, this value is used to calculate the thickness of the sediment at each point. So that the distribution of the thickness value of the sediment at each point is obtained, then a thickness map is made covering the study area. The results showed that in general the research area has a Vs value in the results of the HVSR curve inversion ranging from 130 m/s to 570.83 m/s, Vs average 275.68 m/s. The areas with vs are relatively high in the southern part of Gantiwarno, Wedi, and Bayat subdistricts that are directly adjacent to the hills of Gunung Kidul. Areas with relatively low value vs are in the area of Prambanan Subdistrict, Northern Wedi Subdistrict, Trucuk Subdistrict, Jogonalan Subdistrict, South Klaten District, Central Klaten District, and Kalikotes Subdistrict. For sediment thickness (h) ranges from 5,105 m to 113,648 m. Areas with relatively high sediment thickness are located in parts of Wedi Subdistrict with a thickness of up to 110 m.  Areas with medium thickness (around 60 to 90 m) are in the area of Gantiwarno sub-district, Prambanan district, and the southern part of the Jogonalan sub-district. In the area of Bayat District it has a low thickness (about 5 to 30 m) located in the proves and mountains of the Paseban area and the tomb of Sunan Pandanaran. This shows that areas with high sediment thickness, namely in Wedi District, will also have a high level of earthquake vulnerability.